PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DI DESA HOKU-HOKU GAM KABUPATEN HALMAHERA BARAT - RAY, FRISKA (JURNAL ADMINISTRASI PUBLIK, 2020)
Community participation in development can require a community's ability in community development.Therefore, the fundamental perception of community development is increased democratic participation.Based on the problem, the purpose of this research is to know how community participation in developmentplanning in Hoku-Hoku village Gam West Halmahera Regency.The data analysis techniques used in this study are qualitative data analysis techniques. Data collectiontechniques with observation and interview methods, In depth interview and documentation. The researchinformant is the ones who will be the source of information in this study. The data source and the informantin this study were as many as 7 people.The results show community participation in decision making can be said to be lacking. Communityparticipation in the implementation of activities such as service work or project financed by the Village fundis also very lacking this is conveyed by one of the village devices said that in the implementation of physicalprojects infrastructure does not involve the whole community only a small part of those who have expertiseas a builder. Community participation in the evaluation of development programs can be said to be quitehigh because in various activities including physical development of village infrastructure, the communityhas begun to critically even they do not hesitate-hesitate to report to the authorities if they find the rightsdeviant or the implementation of the activity is not according to the plan set.Keywords: community participation, planning, development